Pemberdayaan Masyarakat melalui Pelatihan Keterampilan Las di Banjar Gria Hita Lingkungan Griya Pagutan Indah Mataram - Made Mara; Made Wirawan; I Wayan Suteja; I Made Nuarsa (Jurusan Teknik Mesin FT Universitas Mataram, 2024)
The improvement of human resources quality is a crucial part of the nation-building process. The quality of human resources plays a pivotal role in supporting the competitiveness of a nation amid global competition. Developing countries, including Indonesia, face complex developmental issues such as poverty, educational backwardness, economic challenges, cultural issues, high unemployment rates, and other social problems. Based on these considerations, we pay serious attention to community development with the aim of guiding and transferring skills that can empower the community towards greater productivity. Skills education and welding training are conducted in collaboration with youth groups, targeting the general community, especially the youth. Through the implementation of this welding training program, we seek to provide learning opportunities for unemployed youth without skills, enabling them to acquire knowledge and skills in line with their talents and interests. Ultimately, it is hoped that the skills gained from welding training can serve as a foundation for employment and even the creation of self-employment or group ventures in the future.